Exploring the Efficacy of Exposure and Response Prevention Therapy on Obsessive Compulsive Disorder - Rhodes, Alyssa (MacEwan University Student eJournal, 2024)
Exposure and response prevention therapy (EX/RP) is a well-established treatment method for combatting intrusive obsessions and repetitive, time-consuming compulsions that classify obsessive-compulsive disorder (OCD). Through therapist encouragement and self-monitoring, individuals confront their compulsive fears, in vivo or imaginal, without the ability to alleviate anxiety through obsessive behaviours. The following paper's purpose is to evaluate the efficacy of this therapy and its components for treating individuals diagnosed with OCD. Research showed that response prevention had a promising impact on those as young as 11. Other research emphasized the positive effects of EX/RP on all ages contingent on patients' ability to adhere to the therapy techniques, specifically response prevention. Moreover, studies have found that this singular type of therapy had more effectiveness and fewer disadvantages than other types of anxiety therapies, biological therapies, or integrative therapies. Cumulatively, the studies supported and affirmed EX/RP as a leading treatment method for OCD on the grounds of its efficacy.